Inhibitory Mechanism of Theaflavin-3,3’-digallate on α-Glucosidase - CAO Yufan, HUANG Wei, CHEN Quming, CAI Weirong (Shipin Kexue)
The mechanism of α-glucosidase inhibition by theaflavin-3,3’-digallate (TFDG) was analyzed using enzyme inhibition kinetics, multi-spectroscopies and molecular docking. The results indicated that the inhibition was reversible and displayed a mixed type of competitive and non-competitive inhibition. TFDG quenched the intrinsic fluorescence of α-glucosidase by forming a complex with it. Thermodynamic parameters suggested that the binding was a spontaneous, endothermic and entropy-increasing process, mainly driven by hydrophobic interactions. The binding enhanced the hydrophobicity near Tyr residue and the polarity around Trp residue, reducing the contents of α-helix, β-sheet and β-turn. Molecular docking revealed that TFDG bound in close proximity to the enzyme’s active site, engaging in two hydrophobic interactions with Phe450 and Trp406 residues, respectively, as well as forming three hydrogen bonds with amino acid residues Asp203, Phe450 and Gln603, respectively. This study provides evidence for the potential of TFDG as a feasible candidate functional factor for the treatment of diabetes.